The effect of functionalization on rice-husks derived carbon quantum dots properties and cadmium removal - Zainal Abidin, N.H. (Elsevier Ltd, 2020)
In this work, functionalized CQDs have been synthesized from rice husks through hydrothermal process by varying the amount of Ethylenediamine (EDA) and ascorbic acid as sources of amine group and carboxyl group, respectively. HRTEM images show the formation of functionalized CQDs with sizes less than 10 nm. XRD analysis shows that CQDs have graphitic structure of (002) plane while their thermal stabilities were analyzed using TGA. FTIR analysis of functionalized CQDs reveals the presence of oxygen containing groups which indicates their higher affinity towards cationic binding. UV Visible spectra show highest peak at around 240 nm which corresponds to electronic transition of CdbndC bond. In addition, XPS analysis shows that atomic percentages of carbon and nitrogen increase when using higher amount of ascorbic acid and EDA. Photoluminescence (PL) properties of CQDs indicate that increasing amount of functionalization agent can tune the intensity, with emission in green region wavelength (495â570 nm). Meanwhile, quenching of PL intensity and reduction in AAS absorbance show that carboxyl and amino functionalized CQDs have the potential in detection of cadmium and more than 70 % removal of cadmium from aqueous solution. The cadmium removal fits the pseudo-second order kinetic model and Freundlich isotherm with kinetic rate of 0.0000243 gmgâ1 minâ1 and maximum adsorption capacity of 332.72 mg/g, respectively. Â© 2020 Elsevier Ltd